2023
DOI: 10.5093/psed2023a6
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Oral Reading Fluency Endurance to Comprehension in an Intermediate Depth Orthography

Abstract: Alphabetic orthographies vary in terms of depth, i.e., in terms of the complexity and consistency of the phoneme-grapheme correspondences (Seymour, 2008). Therefore, they can be classified in a depth continuum, where transparent orthographies (e.g., Finnish) are those that have mainly consistent correspondences between phonemes and graphemes, whereas opaque orthographies (e.g., English) have more complex and inconsistent correspondences. Intermediate depth orthographies, such as European Portuguese, are in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Paige et al (2019), in a study with 1064 US third graders, found that students who could spell and read fluently (i.e., with accuracy, expressiveness, and an adequate reading speed) had a 70% chance of getting good grades in their state reading assessment, against a 20% chance for struggling readers. This study, like many similar studies (e.g., Cadime et al, 2023;Cockerill et al, 2023;Risberg et al, 2023), suggests that failure to develop fluency in elementary students might compromise their school achievement and beyond (Rupley et al, 2020). This fact motivates a strong interest in identifying inexpensive, easily implementable, and scalable remedial interventions.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Paige et al (2019), in a study with 1064 US third graders, found that students who could spell and read fluently (i.e., with accuracy, expressiveness, and an adequate reading speed) had a 70% chance of getting good grades in their state reading assessment, against a 20% chance for struggling readers. This study, like many similar studies (e.g., Cadime et al, 2023;Cockerill et al, 2023;Risberg et al, 2023), suggests that failure to develop fluency in elementary students might compromise their school achievement and beyond (Rupley et al, 2020). This fact motivates a strong interest in identifying inexpensive, easily implementable, and scalable remedial interventions.…”
supporting
confidence: 58%
“…Fumagalli et al (2019) stress that although oral reading is the most common way to measure reading fluency, it only relates to some reading comprehension processes. Still, Salceda et al ( 2020) argue that the reading rate is related to reading comprehension in transparent orthographies such as Spanish (the Portuguese orthography is of Intermediate Depth (Cadime et al, 2023;Seymour et al, 2003)).…”
Section: )mentioning
confidence: 99%
“…In future studies, the assessment of reading motivation should include complementary methodologies, such as qualitative or behavioral assessments. The absence of a measure of reading comprehension is another limitation of this study, considering that comprehension is the ultimate goal of reading and that it depends on reading fluency mastering [38,39]. Future studies should include this measure in order to assess the effects of the intervention program not only on fluency and motivation, but also on comprehension.…”
Section: Discussionmentioning
confidence: 99%